The Role of Tafarkin Tsira Islamic Center Azare on Community Service Delivery: A Focus on Marriage Counseling - Ardo, Adam Muhammad; Muhammad, Adamu Abubakar; Kawu, Garba Sa'adu; Muhammad, Anas Adam; Mashema, Bashir Liman (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2024)
This article examines the TafarkinTsira Islamic Center Azare's extensive marriage counseling programs, which are based on Islamic principles and specially designed to cater to the various requirements of the neighborhood's Muslim population. Pre-marital, post-marital, and conflict resolution counseling are all provided by the center, with an emphasis on teaching couples about their rights and responsibilities, encouraging open communication, and mediating disputes between spouses. Through the use of content analysis, interviews, and a review of prior reports, the activity employs a qualitative methodology to demonstrate how these services have improved community well-being overall, decreased divorce rates, and contributed significantly to marital stability. The activity findings revealed that TafarkinTsira Islamic Center promotes solid and healthy marriages through its counseling programs, which are the cornerstone of stable families and a cohesive community. These services have an effect on more than just a couple; they also help the larger community by fostering social peace, financial stability, and mental health. The importance of religious organizations like TafarkinTsira in tackling social issues and assisting the community by providing faith-based counsel is highly recommended.